Use of lactagogues in breastfeeding for mothers assisted by a health family unit - Anne Françoize Marques da Silva; Maria Aparecida Munhoz Gaiva; Rossana Marchese Bittencourt (Rev Rene)
Maternal milk is the best food for children in their first months of life. However, early weaning is common and the rates of breastfeeding are lower than what is preconized. This is a descriptive study which aimed to identify the lactogogues used by mothers of children up to 1 year of age as support to breastfeeding and who advised its use. Data collection was carried out through the filling in of questionnaires by the mothers of children registered in a Family Health Unit in Cuiaba, Brazil, from April to May, 2010. Results showed that all mothers used lactogogues, irrespective of hypogalactia presence. Lactogogues used were foods, liquids, medications and some procedures and techniques. Advice for the use of lactogogues was mostly given by maternal grandmothers. The socio cultural influence in breastfeeding was evident, especially from people closer to the mother.